Hubungan Panjang Tungkai dan Berat Badan dengan Kecepatan Lari Sprint (100 meter) pada Pemain Sepakbola Di SSB Fortuna dan Persatuan Sepakbola Universitas Muhammadiyah Surakarta - Khoirun Nisa', Maulida; , Wijianto SSt. FT. M. OR (2017)
Background: football players have to master many kinds of basic techniques for football that include dribbling the ball, passing the ball, stopping the ball, heading the ball, and shooting the ball. The important basic techniques are kicking and dribbling the ball. In the ball kicking and dribbling technique, a football player must have good sprint skill. The factors that give contribution for the speed of sprint include physiology factors which consist of leg muscle's strength, the explosion power and flexibility of leg muscle. Whereas, the anatomy factors are consist of height, length, big, wide, and weight of the body. Purpose: to know the correlation between the length of leg and weight with the speed of sprint (100 meters) for football players in SSB Fortuna and UMS Football Club. Research Method: the research method which is used in this research is cross sectional that is descriptive analytic. The populations used are the football players in SSB Fortuna and UMS Football Club for 15-25 years old that amount to 50 people. The technique used for getting the sample is using purposive sampling, so all of population that is 50 people are being the sample. The data normality testing is using Kolmogrov-Smirnov Test. The research finding is analyzed by using Correlation Pearson Product Moment test. Research Finding: the result of Correlation Pearson Product Moment test shows that the result of r for the correlation between the length of leg and the speed of sprint is 0,975. Whereas, the result of r between the weight and the speed of sprint is 0,382. Conclusion: there is a significant correlation between the length of leg and weight with the speed of sprint (100 meters) for football players in SSB Fortuna and UMS Football Club.